Institutional Innovations for Smallholder Agricultural Production Systems in Kenya: A Case of Smallholder Tea Subsector - Mose, George N.; Mbeche, Robert; Ateka, Josiah (European Journal of Sustainable Development, 2016)
The smallholder tea sub-sector which is part of the larger Kenyan tea industry has enjoyed considerable success since its inception in the early 1960s. The planted area under the smallholder system, expanded from 2,522 hectares in 1962 to over 100,000 hectares in 2015; while annual production rose from 1.3 million kgs of green leaf to over 1 billion kgs of green leaf over the same period. Other industrial crops such as coffee, sisal and cotton that previously thrived have struggled to survive under diminished government direct investment in the agricultural sector. The smallholder tea subsector has conversely, managed to endure systemic constraints and challenges to remain competitive. This paper shows that while the relative success of the subsector can be explained by the adoption of modern technologies, there are other relevant factors including policy and institutional that KTDA has embraced to remain competitive. Evidence from the study suggests that innovative institutional arrangements and support systems which have been associated with enhanced farmers earnings. In addition, the participatory governance framework put in place post 2000, innovative approaches to the provision of advisory services and information sharing systems have provided an incentive for smallholder farmers to produce high quality teas that directly translated into better earnings. The presence of participatory governance, innovative and efficient systems that reduce costs and enhance farmers earnings are critical success factors for any smallholder agricultural value chain. Key Words: Institutional innovations, smallholder farmers, farmer organisations, KTDA, Kenya